2015
DOI: 10.1021/acs.macromol.5b01655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polypropylene Glycol 400 (PPG400) on the Micellization and Gelation of Pluronic F127

Abstract: In dilute aqueous solution unimers of Pluronic F127 associate to form micelles. In more concentrated solution, micelles pack to form high-modulus gels. Our interest is the effect of addition of 10–30 wt % low molecular weight PPG400 on the micellization and gelation of solutions of F127. DLS was used to determine the apparent size of the micelles (r h,app). The critical micelle concentration (cmc) using the dye solubilization method of F127 in PPG400 solutions was studied. Visual observation was carried out to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…37,41,47,56,68 Because of replacement of water with oxide precursors, the structure is different from that of F127 micelles in bulk aqueous system, which was reported to be FCC structure with d 110 = 15 nm. 69,70 Spherical micelle formation and assembly into a distorted Im3̅ m mesostructure for F127-templated TiO 2 is in accordance with other literature reports due to its large hydrophilic PEO blocks. 20,47,58,71 It is also consistent with the observation that BCC films oriented in the (110) direction form when silica substrate is used.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…37,41,47,56,68 Because of replacement of water with oxide precursors, the structure is different from that of F127 micelles in bulk aqueous system, which was reported to be FCC structure with d 110 = 15 nm. 69,70 Spherical micelle formation and assembly into a distorted Im3̅ m mesostructure for F127-templated TiO 2 is in accordance with other literature reports due to its large hydrophilic PEO blocks. 20,47,58,71 It is also consistent with the observation that BCC films oriented in the (110) direction form when silica substrate is used.…”
Section: Resultssupporting
confidence: 91%
“…From Figures S1 and S2, we can see that micellar distances in the BCC cubic lattice do not change significantly for a vertical compression ratio of 0.89 (Figure S3). Lattice constants and d -spacing values are consistent with the reported values for F127 templated titania, silica, and alumina. ,,,, Because of replacement of water with oxide precursors, the structure is different from that of F127 micelles in bulk aqueous system, which was reported to be FCC structure with d 110 = 15 nm. , …”
Section: Results and Discussionsupporting
confidence: 81%
“…The transition temperatures of the system can be strongly influenced by both the addition of excipients and drugs. Several studies have analyzed the influence of salts, organic solvents, and drugs on the micellization process, gelation, and in the cloud point of the Pluronic ® F127 solutions [36,[40][41][42][43], using similar experimental tools also applied in the present study, such as: Dynamic Light Scattering (DLS), Transmission Electron Microscopy (TEM), and thermal analysis (TGA and DSC). According to Thapa et al [36], the ability of Pluronic ® F127 to solubilize drugs will depend on its organization in solution-whether it is distributed as unimers (dispersed in the solvent individually) or as micelles.…”
Section: Introductionmentioning
confidence: 99%
“…Various additives like salts, ionic liquids, nonelectrolytes, nanoparticles, surfactants, alcohols, carbohydrates, , and polymers , were reported to change the CMT of different Pluronic systems. ,,, Among these materials, saccharide molecules, which play several important roles in various biological processes, exhibit a significant effect on the aggregation behavior of Pluronics. Kim et al reported lowering of the lower critical solution temperature (LCST) of thermoresponsive polymers in the presence of different saccharides based on the cloud point measurements .…”
Section: Introductionmentioning
confidence: 99%